VISI KEBANGSAAN DALAM PRAKTIK PENDIDIKAN ISLAM MUHAMMADIYAH DI ERA KOLONIAL - Ahmad Syauqi Fuady (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to determine the vision of nationality in the educational practice at Muhammadiyah schools especially in 1912-1923. To answer the research objectives in this article, the authors tracked relevant library sources, both from journal articles, book research results, and other document sources. The results of this study indicate that although Muhammadiyah, which was founded by Ahmad Dahlan, focuses its struggle on the educational aspect, the political aspect of nationalism cannot be completely removed. The national struggle in the form of resistance to the Dutch colonialists carried out by Ahmad Dahlan can be traced in the practice of the school he founded. First, Muhammadiyah schools teach religion other than general science, this is contrary to the religious neutrality of the Dutch government's education style. Second, the purpose of Muhammadiyah education is to produce ulama who have religious and scientific understanding, in contrast to the colonial government's education which was solely to prepare employees. Third, the Muhammadiyah education curriculum is intended to produce future cadres who are able to solve the problems and problems of the community, especially the fate of the people in the colonized country.